Ibn Al-Muqaffa’s Proposal for Taqnīn and its Synchronization with Islamic Law Codification in Indonesia - Sonafist, H.Y.; Efyanti, Yasni; Ramlah, Ramlah; Hamzah, Ali; Faizin, Faizin (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2020)
The research problems addressed in the article are the background story behind Ibn al-Muqaffa’s proposal for taqnīn, the historical background of the creation of the Islamic law codification in Indonesia, and the synchronization of ibn al-Muqaffa’s idea for taqnīn with the codification of Islamic law in Indonesia. The current study aims to unravel the view of Ibn Al-Muqaffa, an Islamic figure, about taqnīn. A biographical study was conducted by doing library research, especially on Ibn Al-Muqaffa’s proposal for taqnīn. The data collection procedure was divided into three parts i.e., orientation, exploration, focus-oriented research. Biographical research is part of a qualitative study that uses data analysis techniques and literature study as the qualitative data analysis as well as content analysis through the historical and textual approach. The results of the study reveal the method of law implementation before and during the lifetime of Ibn Al-Muqaffa which could be described as chaotic, with one of the reasons was because, at the time, the court had not possessed the statute that governed the legal activities other than the Islamic jurisprudence (fiqh) which was used by the judges in accepting, examining, and deciding on cases addressed to them. Therefore, every judge took a decision based on their own ijtihad (an Islamic legal term referring to independent reasoning or the thorough exertion of a jurist's mental faculty in finding a solution to a legal question). Ibn Al-Muqaffa advised the Khalifa Abu Jakfar Al-Manshur to compile the correlated legal reasonings in Islamic jurisprudence in which to be implemented and to be applied as the binding legal force in the form of statutory law which was regulated nationally and to be used as guidance by all the judges without no exception. The codification of Islamic law in Indonesia has received a constitutional status based on philosophical, sociological, and juridical reasons. The researchers closely examine three types of Islamic legal laws i.e., Act number 7 of 1989, Act number 3 of 2006, and Act number 50 of 2009 concerning Religious Courts, Act number 41 of 2004 concerning Waqf (Endowment), and Act number 21 of 2008 concerning Sharia (Islamic) Banking. Taqnīn (the codification of Islamic law) must be adjusted to demands of the present time in which it is implemented and in accordance with the specific fields of law, for example, taqnīn for Civil Law, Criminal Law, Family Law, Judicial Law, State Administrative Procedure Law, State Administrative Law, And State Finances.